Persepsi Guru Sekolah Dasar Terhadap Penelitian Tindakan Kelas Untuk Karir Profesional - Adri, Helmia Tasti; Fauziah, R. Siti Pupu; Suherman, Irman; Sesrita, Afridha; Indra, Syukri; Syamsudin, Didin; Sudjani, Desky Halim (LPPM Universitas Mohammad Husni Thamrin, 2022)
AbstractThe research background is the situation of motivated, interest and ability of teachers in elementary schools in compiling and producing classroom action research to support their professional careers as a professional teachers is in under qualities. The purpose of this study was to determine teacher perceptions of the importance of classroom action research scientific work for professional teachers. The method used in this research is descriptive study. Collection data is using some instruments such as questionnaires, interviews, observation and documentation to 40 teachers of Amaliah Ciawi Elementary School, Bogor Regency, West Java, Indonesia. The finding data of the research is some teachers is in good ability to writing CAR, some others still not really understand about how to impelementation CAR, but only in beginning of knowledge. Regarding the importance of CAR for teachers, some teachers state that classroom action research is very important for teachers' professional careers. Meanwhile, the teacher's perception of the importance of classroom action research was obtained from open questionnaire data and the results showed that most teachers had the same positive perception, that classroom action research was very important for teachers. The conclusion from this study is that teachers have different perceptions of the importance of classroom action research for professional teachers, but most of these perceptions are guided by data that lead to positive perceptions.